A new genus and five new species of arboreal tarantulas (Araneae: Theraphosidae) from Brazil - Borges, Leandro Malta; Abegg, Arthur Diesel; Paladini, Andressa; Bertani, Rogério (Zootaxa, 2025)
We describe the new genus Arboriticus gen. nov. and five new species of tarantulas from southeastern and northeastern Brazil: Arboriticus celsoi gen. nov. sp. nov. (type species) with male and female, A. petropolis gen. nov. sp. nov. with male, A. minor gen. nov. sp. nov., with male, A. giganteus gen. nov. sp. nov. with male and female, and A. maculatus gen. nov. sp. nov. with both male and female. Eupalaestrus spinosissimus Mello-Leitão, 1923 is transferred to Arboriticus gen. nov., making the new combination A. spinosissimus (Mello-Leitão, 1923). Eupalaestrus tarsicrassus Bücherl, 1947 is removed from the synonymy with Eupalaestrus spinosissimus and transferred to Arboriticus gen. nov. making the new combination A. tarsicrassus (Bücherl, 1947). The male of A. tarsicrassus is described for the first time. Pamphobeteus holophaeus Mello-Leitão, 1923 is removed from the synonymy with Eupalaestrus spinosissimus, transferred to Vitalius Lucas, Silva Junior & Bertani, 1993, and considered a junior synonym of Vitalius dubius (Mello-Leitão, 1923). The new genus is supported by phylogenetic evidence based on morphological and behavioral characters. The basal position of the genus in the available cladogram, along with its diverse morphology, indicates that Arboriticus gen. nov. species diverged early during the evolution of an important clade of theraphosines in Brazil and may represent relict populations. The most striking feature of these species is their arboreal habit, which is unusual among theraphosines. Due to the endemism of these species in heavily impacted and deforested regions formerly covered by the Brazilian Atlantic Forest, their arboreal nature, and the rarity of specimens, the species of Arboriticus gen. nov. can be considered threatened, and conservation efforts for their protection are strongly recommended.